Interseksionalitas Pengalaman Perempuan Toraja: Sebuah Konstruksi Teologi Feminis Melalui Ritus Ma’ Bua’ Kasalle - Vani Mega Rianna Mantong Tendenan (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2021)
This paper discusses the Toraja ritual, namely ma' bua' kasalle as a life thanksgiving ceremony which then becomes the basis for offering a feminist theological perspective, regarding the intersectionality of women's experiences in ritual. The method used in this article is a qualitative method with an analytical description approach that brings together Ronald L. Grimes' thoughts on ritual as a bodily experience with Denise L. Carmody's thoughts on women's experiences rooted in the experience of the Christian faith. The aim is to provide a feminist theological perspective that the intersectionality in the experience of Toraja women results in an attempt at equality in cultural rituals such as ma' bua' kasalle. The results show that the intersectionality of the experiences of Toraja women occurs through the first pa'gellu' dance, the second group of nani and simbong songs and the third is the placement of the fallen women who are in the tower. The three representations have created a dynamic and inclusive space for action, language, and relations. The interaction between the experiences of Toraja women is a source of self-empowerment and community. The thesis statement of this paper is that the intersectionality of the Toraja women's experience means a social interaction that involves the role of women with all their existence including faith, perspective, and presence as an effort to equal women in culture.Tulisan ini membahas tentang ritual Toraja yaitu ma' bua' kasalle sebagai upacara syukuran kehidupan yang kemudian menjadi dasar untuk menawarkan perspektif teologi feminis, tentang interseksionalitas pengalaman perempuan dalam ritual. Metode yang digunakan dalam artikel ini ialah metode kualitatif dengan pendekatan deskripsi analitis yang mempertemukan pemikiran Ronald L. Grimes tentang ritual sebagai pengalaman tubuh dengan pemikiran Denise L. Carmody tentang pengalaman perempuan yang berakar pada pengalaman iman Kristen. Tujuannya adalah untuk memberikan perspektif teologis feminis bahwa interseksionalitas dalam pengalaman perempuan Toraja menghasilkan upaya kesetaraan dalam ritual budaya seperti ma' bua' kasalle. Hasil penelitian menunjukkan interseksionalitas pengalaman perempuan Toraja terjadi melalui pertama tari pa'gellu', kedua kelompok nyanyian nani dan simbong dan ketiga adalah penempatan tumbang perempuan yang berada di menara. Ketiga representasi tersebut telah menciptakan ruang aksi, bahasa dan relasi yang dinamis dan inklusif. Interaksi antar pengalaman perempuan Toraja menjadi sumber pemberdayaan diri dan komunitas. Pernyataan tesis makalah ini ialah interseksionalitas pengalaman perempuan Toraja berarti suatu interaksi sosial yang melibatkan peran perempuan dengan segala keberadaan dirinya termasuk iman, perspektif dan kehadirannya sebagai upaya kesetaraan perempuan dalam budaya.